A.I.D Sweat Patches / Nurul Izzati Parman, Siti Nur Ayuni Rokhaizin … [et al.] - PARMAN, NURUL IZZATI; ROKHAIZIN, SITI NUR AYUNI; JOHARI, NOR ADIBAH; IBRAHIM, AMY FARHAH; ZAINAL ARIFIN, FATIN ELYANl (2016)
A.I.D Biosensor Sweat Patch innovation is to encourage and help people maintain their health. This product suitable for active person at age 25 years old until 64 years old. The concept of our product is simple where a sweat path with a biosensor will be put under customer armpit and it will be connect to the application in their smartphone. Through the application and product features, it can overcome sweat problem, body odor and analyze body water level, electrolyte level, glucose level and protein level. Thus, it will be easier for them to know and detect whether they are healthy or opposite.